Abstract 6440: Effects of cumulative tobacco exposure on lung cancer genomic profiles in Latin Americans - Javiera Garrido; Evelin González; Alejandro Blanco; Gonzalo Sepúlveda-Hermosilla; Matias Freire; Rivas Arenas Solange Mariela; Katherine Marcelain; Gareth I. Owen; Carolina Ibañez; Alejandro H. Corvalan; Marcelo Garrido; Rodrigo Assar; et al. (American Association for Cancer Research (AACR), 2026)
Abstract Motivation: Tobacco exposure is a major determinant of tumor genomic landscapes in non-small cell lung cancer (NSCLC). Two of the most clinically relevant actionable genes in lung cancer, EGFR and KRAS, show opposite patterns, with smokers exhibiting a higher prevalence of alterations in KRAS and never-smokers in EGFR. Yet, the dynamic and evolution of genomic changes as a function of cumulative tobacco exposure has received limited attention. Here, we examine how tumor genomic profiles vary according to smoking intensity, duration, and time since cessation (TSC). Our study focuses on an underrepresented population of Latin American patients, where additional research is needed to better characterize tumor heterogeneity. Methodology: The population was obtained from the protocol Characterization and Validation of Molecular Diagnostic Technologies for Lung Cancer Patients from Chile, Brazil, and Peru. Participant recruitment was between July 2015 and October 2018 across 37 different centers. Primary or metastatic NSCLC specimens were analyzed, and genomic profiles were generated with the Oncomine Focus Assay (OFA). A total of 1,864 participants yielded QC-approved genomic profiles. Covariates of interest were assessed at enrollment. Cumulative tobacco exposure, including smoking intensity (cigarettes per day), duration, and TSC, was quantified using the Comprehensive Smoking Index (CSI). In addition, smoking status (current vs. never) was recoded as a function of TSC in order to identify the time period during which major genomic alterations (GA) are most likely to occur. Descriptive statistics, generalized linear models, and generalized additive models were used to evaluate the association between CSI and the prevalence of GA across genes. All models were adjusted for potential confounders, including country, age, sex, NSCLC subtype, cancer stage and history of cancer. Results and Conclusions: A total of 1100 patients had complete genomic and tobacco exposure information. Among current smokers, median smoking intensity and duration were 20 cigarettes per day and 48 years, respectively, compared with 30 cigarettes per day and 47 years among former smokers. Ninety percent of former smokers had ceased tobacco use at least 10 years prior to diagnosis, with a median TSC of 1 year. CSI analysis identified 14 genes significantly associated with genomic alteration status, including EGFR, PIK3CA, ALK, MTOR, ERBB3, and RET. Higher CSI values (4th quartile) showed approximately double the frequency of genomic alterations compared with the lowest CSI quartile for ALK (16.2% vs. 8.7%), RET (12.8% vs. 6.9%), and MTOR (15% vs. 6.9%). Mid-range CSI values exhibited the lowest prevalence of alterations in EGFR (12.6% vs. 31%) and PIK3CA (6.9% vs. 14.5%). Overall, these findings support the value of CSI in refining exposure-genotype associations and the need for improves risk stratification efforts in diverse populations. Citation Format: Javiera Garrido, Evelin González, Alejandro Blanco, Gonzalo Sepúlveda-Hermosilla, Matias Freire, Solange Rivas, Katherine Marcelain, Gareth I. Owen, Carolina Ibañez, Alejandro H. Corvalan, Marcelo Garrido, Rodrigo Assar, Rodrigo Lizana, Javier Cáceres-Molina, Diego Ampuero, Liliana Ramos, Paola Pérez, Osvaldo Aren, Sara Chernilo, Cristina Fernández, María Loreto Spencer, Jacqueline Flores, Giuliano Bernal, Mónica Ahumada Olea, Germán Rasse, Carolina Sánchez, Maria Galli de Amorim, Emmanuel Dias-Neto, Helano C. Freitas, Ricardo Armisen. Effects of cumulative tobacco exposure on lung cancer genomic profiles in Latin Americans [abstract]. In: Proceedings of the American Association for Cancer Research Annual Meeting 2026; Part 1 (Regular Abstracts); 2026 Apr 17-22; San Diego, CA. Philadelphia (PA): AACR; Cancer Res 2026;86(7 Suppl):Abstract nr 6440.